The Effectiveness of Tea Tor Bangun With the Level of Breast Milk Production in Breastfeeding Mothers at the Ciledug Health Center - Olivia Nency; Humairoh Humairoh (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background: In general, newborns will breastfeed 10-12 times every 24 hours or even 18 times, which is very important for their growth and development. Purpose of Writing: To find out the effectiveness of Tea Tor Bangun With the Level of Milk Production in Breastfeeding Mothers at the Ciledug Health Center . Research Methods: This study used a pre-experimental method with a one group pre-posttest design approach. This study used an experimental methodology with a posttest-only and non-equivalent groups design. The research sample consisted of 40 participants who were divided into two groups: the intervention group who received torbangun tea with 20 participants, and the control group who did not receive torbangun tea with 20 participants. The sample selection technique was not based on purposive sampling probability. Results: The results of the Asimp study showed that Sig (2-Talled) in the intervention group was 0.000 and 0.034 in the control group. The hypothesis is accepted because 0.000 < 0.05 and 0.034 < 0.005. This shows that the increase in milk production of breastfeeding mothers in the intervention group and the control group is different. However, the P-values ​​were higher when the intervention and control groups were compared. According to statistical findings, Tea Tor Bangun was more effective in the intervention group when compared to the control group in terms of the level of milk production in breastfeeding mothers at the Ciledug Health Center. one of the non-pharmacological types by giving torbangun tea leaves.